A low latency SISO with application to broadband turbo decoding - Beerel, P.A.; Chugg, K.M. (IEEE journal on selected areas in communications, 2001)
The standard algorithm for computing the soft-inverse of a finite-state machine [i.e., the soft-in/soft-out (SISO) module] is the forward-backward algorithm. These forward and backward recursions can be computed in parallel, yielding an architecture with latency /spl Oscr/(N), where N is the block size. We demonstrate that the standard SISO computation may be formulated using a combination of prefix and suffix operations. Based on well-known tree-structures for fast parallel prefix computations in the very large scale integration (VLSI) literature (e.g., tree adders), we propose a tree-structured SISO that has latency /spl Oscr/(log/sub 2/N). The decrease in latency comes primarily at a cost of area with, in some cases, only a marginal increase in computation. We discuss how this structure could be used to design a very high throughput turbo decoder or, more generally, an iterative detector. Various subwindowing and tiling schemes are also considered to further improve latency.